Letter to Jane Tolmach from May Layne Bonnell - May Layne Bonnell:::::: (1960)
A letter to Jane Tolmach from May Layne Bonnell that informs her about the appointment of Harold Nason to the Board of Directors of the 31st District Agricultural Association.